(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
This article is devoted to the development of reading competence of students, which focuses on the importance of reading in teaching and learning a foreign language, the types and objectives of reading, which is one of the types of speaking activities. The development of reading competence in the learning processwas demonstrated by the method of "Stationenlernen". This method, as an interactive method, encourages the student to work independently by integrating all speech activities in the classroom and the teacher acts as an observer in the classroom. The various assignments recommended to the students ensure that the students actively participate in the lesson.